Hydride Migration from a Triangular Face to a Tetrahedral Cavity in Tetranuclear Iron Carbonyl Clusters upon Coordination of [AuPPh3]+ Fragments1. Issue 28 (21st May 2014) - Bortoluzzi, Marco; Ciabatti, Iacopo; Femoni, Cristina; Hayatifar, Mohammad; Iapalucci, Maria Carmela; Longoni, Giuliano; Zacchini, Stefano
Abstract Metal hydrides are of fundamental importance in chemistry, both as solid‐state materials and molecular compounds. The first low‐valent molecular metal cluster containing an interstitial four‐coordinate hydride in a tetrahedral site is decribed, which undergoes hydride migration from the surface to the tetrahedral cavity of the cluster upon coordination of a [AuPPh3]+ fragment. The [HFe4(CO)12(AuPPh3)2]− mono‐anion, which contains a surface μ3‐H, was obtained from the reaction of [HFe4(CO)12]3− with two equivalents of [Au(PPh3)Cl]. This is, in turn, transformed into the neutral [HFe4(CO)12(AuPPh3)3] upon addition of a third [AuPPh3]+ fragment, with concomitant migration of the unique hydride from the surface of the cluster to its tetrahedral cavity. All of these species have been fully characterized in solution by means of IR and multinuclear NMR spectroscopy, and in the solid state by single‐crystal X‐ray diffractometry.